Pembelajaran bahasa Arab menerusi rancangan al-Arabiyyah fi al-radio: analisis awal pendengar - Nasir, Mohd Shahrizal; Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus (Penerbit UTM Press, 2015)
The teaching and learning of Arabic in Malaysia have undergone positive transformations; from its humble beginning in the madrasah and sekolah pondok (both refer to specific type of religious school) to becoming one of the main subjects in primary schools with the introduction of the j-QAF teaching module (acronym for Jawi, Quran, Arabic and Fardu Ain). In fact, the Arabic language programme is offered both at the degree and postgraduate levels in several higher learning institutions. Currently, with Malaysia becoming more technologically advanced, the teaching of Arabic language has become accessible for people of all ages and background via television, radio and the internet. This research focuses on the general public’s response towards learning Arabic through radio, with particular emphasis on the listeners of a radio show entitled Al-Arabiyyah Fi Al-Radio (Arabic through the Radio) that is currently aired on Radio Malaysia TerengganuFM channel. The main objective of this preliminary study is to improve the quality of the programme through the audiences’ recommendations and suggestions. This is a quantitative study of 105 respondents from a survey made available on the Al-Arabiyyah Fi Al-Radio Facebook® page and the TerengganuFM Facebook® page. The results revealed that, in their attempt to learn and master Arabic, the listeners have benefited from the content presented in the programme. Several suggestions were also made to improve the quality of learning Arabic through the programme.